Risk factors for Clostridioides difficile infection in hospitalized patients and associated mortality in Japan: a multi-centre prospective cohort study. Issue 3 (March 2020) - Honda, H.; Kato, H.; Olsen, M.A.; Reske, K.A.; Senoh, M.; Fukuda, T.; Tagashira, Y.; Mahe, C.; Dubberke, E.R.
Summary: Background: Although population characteristics and antimicrobial prescribing practices suggest that the hospitalized population in Japan is at high risk of Clostridioides difficile infection (CDI), the epidemiology of CDI in Japan is poorly understood. Aim: This prospective cohort study aimed to investigate the epidemiology of CDI at 12 hospitals in Japan. Methods: Patients with clinically significant diarrhoea (CSD) were enrolled. Stool specimens were tested for C. difficile by toxin A and/or B enzyme immunoassay (EIA) in the hospital laboratories, and a toxigenic culture and nucleic acid amplification tests were performed at a central laboratory. The risk factors of CDI and the impact of CDI on mortality were investigated. Findings: In total, 566 patients with CSD were included in the analyses. A total of 152 patients received the diagnosis of CDI by Toxin A/B EIA, toxigenic culture, or nucleic acid amplification test. Factors associated with CDI included low albumin (adjusted odds ratio (aOR): 1.56; 95% confidence interval (CI): 1.03–2.34) and length of hospital stay before stool collection >18 days (aOR: 1.73; 95% CI: 1.09–2.75). CDI was associated with an increased mortality on univariate analysis (OR: 1.6, 95% CI: 1.0–2.6) but was not associated with an increased risk of mortality on multivariable analysis. Conclusion: Risk factors for CDI in Japan were similar to those identified in the USA and Europe. However, CDI was not associated with an increased risk of mortality in this population of patients with CSD.